Plant Nitrogen status driving soil organic matter mineralization in the rhizosphere - Colocho Hurtarte, Luis Carlos (Universidade Federal de Viçosa, 2016)
The factors that regulate the dynamics of soil Carbon (C) and Nitrogen (N) in the rhizosphere are still poorl y understood. The soil C mineralization in the rhizosphere ca n be heavil y influenced by plant’s nutritional status, atmospheric CO2 concentration and temperature, among others. In this study, we assess the influence of Eucalyptus spp. N status on the C and N dynamics in the rhizosphere. We performed an experiment us ing two compartment rhizobox. In the upper compartment, plants were cultivated in washed sand and supplied with a solution containing all nutrients or all nutrients but N. The lower compartment limited the contact of the roots with the soil using a 5 μm mesh nylon membrane. We observed a higher root-shoot ratio for the N deficient plants and an increase in its soil CO2 concentration. The roots of the –N planted treatment had higher concentrations of citrate and tallose and lower concentration of sucrose and aminoacids, when compared to the +N planted treatment. The C and N anal ysis of the mineral associated organic matter fraction, together with the thermochemol ysis data showed an increase in C mineralization in both planted treatments and changes in N dynamics. As the roots had no physical contact with the soil due to the nylon membrane, the changes in the soil must have been consequence of root exudation. The contrasting sugar and aminoacid root content, together with the citrate concentration in soil solut ion extract and the C mineralization data, indicate that exudate composition changed due to the plants N status. The data indicates that the plants in the –N treatment exudated more organic acids than the plants of the +N treatment. Still the exudate comp osition of the plants with the +N treatment may had a higher energetic content and thus affected differentl y the soil microbial communities. The δ13C data indicate that the N deficient plants affected a higher volume of soil than the plants of the +N treatment. All this together shows different priming mechanisms were dominant due to the plants N status. As the plants were N deficient, the mineralization of soil C was driven by the “N-mining” mechanism while in the soil of the +N planted treatment the dominant mechanism was “microbial stoichiometry”. This work demonstrates, to our knowledge, by the first time using the same plants, different priming mechanisms due to the plants N status. Thus highlighting, the importance of plants nutrient management in the rhizosphere C dynamics.

Os fatores que regulam a dinâmica do Carbono (C) e Nitrogênio (N) do solo na rizosfera são ainda pouco compreendidos. A mineralização de C na rizosfera pode ser fortemente influenciada pelo estado nutricional da planta, a concentração de CO2 na atmosfera e a temperatura do ambiente, entre outros. Em este estudo, avaliamos o status nutricional de N em plantas de Eucalyptus spp. e sua influência na dinâmica do C e do N n a rizosfera. Realizamos um experimento usando um rhizobox dividido em dois compartimentos. No compartimento de cima plantas foram cultivadas e areia lavada e supridas com uma solução nutritiva contendo todos o nutrientes e a mesma solução porém sem N . No compartimento inferior o contato das raízes com o solo foi limitado usando uma membrana de nylon com abertura de 5 μm. Observamos uma maior razão raiz:parte aérea e maiores concentrações de CO2 no solo das plantas com deficiência de N. As raízes das plantas deficientes em N, apresentaram maiores concentrações em relação as plantas não deficientes em N, de citrato e tallose, e menores concentrações de sucrose e aminoácidos. A análise de C e N da fração de matéria orgânica ligada aos minerais , junto com os dados obtidos pela termoquimolise indicam um aumento na mineralização de C e uma modificação na dinâmica do N. Devido a impossibilidade de contato físico direto com o solo, pela presença da membrana de nylon, a única forma de modificar o solo seria então pela exsudação de compostos pelas raízes. O contrastante conteúdo de aminoácidos e açúcares na raiz, junto com os dados do extrato da solução do solo e de mineralização de C, indica que a composição destes exsudatos diferiu em razão da deficiência de N. Enquanto as plantas deficientes em N exsudaram mais ácidos orgânicos, as plantas com ótimo status nutricional foram capazes de exsudar compostos energeticamente ricos. Os dados de δ13C da matéria orgânica ligada aos minerais indica que as plantas deficientes em N afetaram um maior volume de solo que as plantas supridas de N. Tudo isto mostra que, diferentes mecanismos de efeito priming foram dominantes, dependendo do status nutricional da planta. Em plantas deficiente de N, a mineralização de C no solo foi dominada pelo mecanismo chamado de “mineração de N”, enquanto no solo das plantas supridas de N o mecanismo dominante foi a “estequiometria microbiana”. Este trabalho demostra pela primeira vez, ao nosso saber, a atuação de diferentes mecanismos de efeito priming n a mesma planta, sobre diferente status de N . Assim ressaltando, a importância do manejo de nutrientes na dinâmica do C da rizosfera.
Os fatores que regulam a dinâmica do Carbono (C) e Nitrogênio (N) do solo na rizosfera são ainda pouco compreendidos
Keywords: Plantas e solo; Solos florestais; Solos - Teor de compostos orgânicos; Solos - Humus; Eucalyptus ssp.; Plantas - Metabolismo; Ciência do Solo